Saturdays of Science. An Experimental Learning and Training Scenario in CLIL and IBSE: A Case Study - Mata-Torres, Susana; Sanz de la Cal, Esther; Greca, Ileana M. (Frontiers in Education, 2022)
We present a case study where the use of both Content and Language Integrated Learning (CLIL) and Inquiry-Based Science Education (IBSE) can be observed and studied as a hybrid methodology applied in a non-formal context in primary education. The context is the teaching of science in a Foreign Language (English) and the aim is to determine didactic strategies that are useful for improving teaching/learning processes. It is conducted in the non-formal context of science workshops, known as Saturdays of Science. 102 children in primary education attended the workshops, at which both the CLIL and the IBSE approaches were combined and which were supervised by 17 future teachers of primary education. The workshops were observed and analysed together with the changes introduced in the methodology and in the successive improvements to the teaching experience, examining the way in which they influenced the perceptions of the children and the future teachers. These results offer useful strategies for teachers in charge of CLIL teaching in primary education.